2020
DOI: 10.1111/1748-8583.12297
|View full text |Cite
|
Sign up to set email alerts
|

Mind the channel! An affordance perspective on how digital voice channels encourage or discourage employee voice

Abstract: We apply an affordance lens on qualitative data from three case organisations using a digital voice channel providing employees with the opportunity to speak up via answering periodic mini‐surveys and making comments in an anonymous mini‐forum. We find that imbrications of material and social agencies (i.e., the voice channel's features and managerial reactions to voice) in the respective organisational contexts culminate in employees perceiving the channel as either affording or constraining voice, leading to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 35 publications
1
44
0
Order By: Relevance
“…The di erent ways users -including organizations' management teams and ordinary stakeholders -perceive a ordances can thus a ect the communication process that bears critical consequences for business success. In this sense, the current paper also echoes with some new management literature that examined external and internal communication challenges from the a ordances perspective (e.g., Argyris & Monu, 2015;Ellmer & Reichel, 2020), and argues that scholars should consider incorporating a ordance theory into their empirical inquiries to better understand why organizations behave in a certain way on social media. In fact, recent insights from Davies and Hobbs (2020) have found that digital media's a ordances can sometimes encourage or nudge social media in uencers to engage in propagandistic communication practice and violate the normative guidelines of ethical public relations (Kent & Li, 2020), without serious rami cations from regulatory entities.…”
Section: Discussionsupporting
confidence: 58%
“…The di erent ways users -including organizations' management teams and ordinary stakeholders -perceive a ordances can thus a ect the communication process that bears critical consequences for business success. In this sense, the current paper also echoes with some new management literature that examined external and internal communication challenges from the a ordances perspective (e.g., Argyris & Monu, 2015;Ellmer & Reichel, 2020), and argues that scholars should consider incorporating a ordance theory into their empirical inquiries to better understand why organizations behave in a certain way on social media. In fact, recent insights from Davies and Hobbs (2020) have found that digital media's a ordances can sometimes encourage or nudge social media in uencers to engage in propagandistic communication practice and violate the normative guidelines of ethical public relations (Kent & Li, 2020), without serious rami cations from regulatory entities.…”
Section: Discussionsupporting
confidence: 58%
“…The social dynamics and evolvement of technology are rarely captured in sufficient details in e-HRM studies which does not help to resolve the question of how users and what of technology matter for the production of successful consequences. Notable exceptions to this dominant conceptualisation (Dery et al, 2013;Ellmer & Reichel, 2020;Francis et al, 2014;Wiblen, 2016) view technology as an active actor playing an equally important role alongside social activities in producing and reproducing HRM practices while being an inseparable part of those practices (Ellmer & Reichel, 2018.…”
Section: Causal Assumptionsmentioning
confidence: 99%
“…While the sociomaterial perspective has already received some attention in research on e-HRM, this has mostly been in the context of broader reviews or conceptual papers discussing future research Bondarouk & Brewster, 2016), when speculating about conflicting results of empirical studies (Marler & Parry, 2016), or in reference to current conceptualisations of technology (Ellmer & Reichel, 2018;Marler & Fisher, 2013;Strohmeier, 2009). However, with a couple of notable exceptions (Dery et al, 2013;Ellmer & Reichel, 2020;Wiblen, 2016), the sociomaterial perspective has not been integrated into empirical e-HRM research. Next, the sociomaterial perspective on e-HRM is presented as a promising way of reconceptualising technology, actors and HRM practices in ways that help to address many of the limitations described in the previous section.…”
Section: Sociomaterials Perspectives On E-hrmmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge transfer is emphasized as a strategic issue for sustainable competitive advantage of an organization ( Zhang and Jasimuddin, 2008 ; Jasimuddin and Zhang, 2009 ; Jasimuddin and Zhang, 2011 ). Contrarily, knowledge hiding is a counter-productive workplace behavior that has significant negative consequences on organizational performance ( Huo et al, 2016 ; Jiang et al, 2019 ; Ellmer and Reichel, 2021 ; Xiong et al, 2021 ). Knowledge hiding was negatively associated with creativity of an organization ( Černe et al, 2014 ; Rhee and Choi, 2017 ; Xiong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%